GRACED: A Novel Fragile Watermarking for Speech Based on Endpoint Detection. (4th October 2022) - Zhou, Shuyun; Song, Meixin; Qian, Qing; Liao, Wenjing; Gong, Xiaofeng
Abstract : Content authentication and tampering detection of multimedia is a vital application by using digital watermarking. In this paper, we propose a novel fraGile wateRmArking of speeCh based on Endpoint Detection (namely GRACED) to verify the integrity of speech. Firstly, speech signal is framed word by word and each speech frame includes one intact nonsilence word. Subsequently, feature fusion is adopted to generate the fragile watermark which will be embedded into the coefficients of hybrid domain of discrete wavelet transform (DWT) and singular value decomposition (SVD). Finally, the tampering detection is accomplished without using any synchronous code to detect kinds of attacks. Several experiments are executed in order to quantify the performance of the proposed method. Experimental evaluation and comparisons with other schemes demonstrate that the signal-to-noise ratio of the proposed method is high with a favorable imperceptibility. Additionally, the tampering localization of various malicious attacks can be achieved without using synchronous code and the proposed scheme even can determine the attack types.